STRATEGI ADAPTASI PETENUN SONGKET SILUNGKANG DI DESA SILUNGKANG OSO KECAMATAN SILUNGKANG KOTA SAWAHLUNTO - Fajrin, Fajar; Marnelly, T. Romi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to determine the efforts or strategies undertaken by Silungkang songket weavers in Silungkang Oso Village in maintaining their business in order to develop and compete. The researcher chose the research object because the business of the Silungkang songket weaver in Silungkang Oso Village has shown its existence until now, so that the Silungkang Songket weaving has become a superior product by the Sawahlunto City Government. The theory used in this research is adaptation strategy theory which is then divided into active strategy, passive strategy and network strategy. An active strategy is a strategy that optimizes all potential to carry out your own activities and look for other job opportunities. Passive strategy is a strategy that only uses one goal without any change in its achievement. Meanwhile, the network strategy is a strategy that includes both formal and informal relationships and relationships in the surrounding environment. In this study, the subject-taking technique used a purphosive sampling technique whose criteria had been determined in this study. This study used a qualitative analysis that discusses the efforts and strategies of songket weavers in Silungkang Oso Village. The results of this study are in the active strategy of the informants trying to maximize their potential and even looking for other jobs to meet their needs. In the passive strategy, the informant only depends on the situation without any more effort in his work. Meanwhile, in the network strategy, informants build relationships with various parties related to their workÂ Keywords: Adaptation Strategies, Songket Weaving Business